Complete Genome Sequence of Mesorhizobium ciceri Strain CC1192, an Efficient Nitrogen-Fixing Microsymbiont of Cicer arietinum. - Haskett, T.; Wang, P.; Ramsay, Joshua; O'Hara, G.; Reeve, W.; Howieson, J.; Terpolilli, J. (American Society for Microbiology, 2016)
We report the complete genome sequence of Mesorhizobium ciceri strain CC1192, an efficient nitrogen-fixing microsymbiont of Cicer arietinum (chickpea). The genome consists of 6.94 Mb distributed between a single chromosome (6.29 Mb) and a plasmid (0.65 Mb).